Transforming Rice Breeding: Re-Designing the Irrigated Breeding Pipeline at the International Rice Research Institute (IRRI). Issue 1 (2019) - Collard, Bertrand C.Y.; Gregorio, Glenn B.; Thomson, Michael J.; Islam, Md. Rafiqul; Vergara, Georgina V.; Laborte, Alice G.; Nissila, Eero; , Tobias Kretzschmar; Cobb, Joshua N.
No abstract available